Penguatan Solidaritas Sosial Melalui FGD Pada Santri di Pondok Pesantren Waria Al-Fatah Kotagede Yogyakarta - Dyaloka Puspita Ningrum (Jurnal Surya Masyarakat, 2021)
The existence of waria is often constructed as a marginal group which results in the emergence of discriminatory attitudes in society. On the other hand, the phenomenon that hit the transgender group also intersects with the humanist values of "how to humanize humans" which need to be supported without any differences between each other based on the contents of the 1945 Constitution Article 28D concerning Human Rights, including at the Waria Al Islamic Boarding School. -Fatah in Kotagede Yogyakarta, which was formed in 2008. This activity was attended by 22 participants with the aim of strengthening the social solidarity of the students in achieving group harmony, especially during the current covid-19 pandemic. Using the FGD / focus group discussion method and lectures related to understanding digital media literacy as a trend that transgender students can pursue to brand themselves and promote their respective businesses in a more modern way. The results of the activity show that there are discomforts encountered by the students when worshiping in public places, even though the group has the same needs as other humans, including spiritual desires / impulses. So that through this boarding school they are also given space to worship for their own reasons. The existence of community service at the Waria Al-Fatah Islamic Boarding School is expected to further strengthen tolerance with a focus on inter-religious spiritual activities.The existence of waria is often constructed as a marginal group which results in the emergence of discriminatory attitudes in society. On the other hand, the phenomenon that hit the transgender group also intersects with the humanist values of "how to humanize humans" which need to be supported without any differences between each other based on the contents of the 1945 Constitution Article 28D concerning Human Rights, including at the Waria Al Islamic Boarding School. -Fatah in Kotagede Yogyakarta, which was formed in 2008. This activity was attended by 22 participants with the aim of strengthening the social solidarity of the students in achieving group harmony, especially during the current covid-19 pandemic. Using the FGD / focus group discussion method and lectures related to understanding digital media literacy as a trend that transgender students can pursue to brand themselves and promote their respective businesses in a more modern way. The results of the activity show that there are discomforts encountered by the students when worshiping in public places, even though the group has the same needs as other humans, including spiritual desires / impulses. So that through this boarding school they are also given space to worship for their own reasons. The existence of community service at the Waria Al-Fatah Islamic Boarding School is expected to further strengthen tolerance with a focus on inter-religious spiritual activities.